KARAKTERISTIK KITAB HADIS SABÄªL AL-SALÄ€M LI BULÅªGH AL-MARÄ€M KARYA SULTAN MUHAMMAD IDRUS BUTON SULAWESI TENGGARA - Faridi, Faridi; Fauziah, Gina; Rahman, Cep Mochamad Faqih Fatwa; Rohaniah, Eni (Jurnal Studi Hadis Nusantara, 2023)
Not many kings are also scholars. Not many scholars are also writers. Sultan Muhammad Idrus is a rare figure. He was a sultan (king) who had producedÂ  numerous works in the fields of religion and literature. If all of his works were calculated, they would total more than fifteen. One of his works that needs to be shown to public is SabÄ«l al-SalÄm li BulÅ«gh al-MarÄm. This book is still manuscipt form. The research method used by the author in this article employs a method of library research. This research reveals several characteristics of the manuscript form of SabÄ«l al-SalÄm li BulÅ«gh al-MarÄm, Those are, first, the themes addressed in this hadith book, namely, targhÄ«b wa tarhÄ«b, and second, the hadiths are mentioned in short version without including their transmission system (sanad) except for those at the level of companions. Third, the hadiths are not solely derived from the al-kutub al-tisâ€™ah, but also from other sources of hadith books. Additionally, it places the topic of sincerity (ikhlÄá¹£) not in the first chapter.